Simulation of three phase switched reluctance motor by using xcos / Ernie Syazwanie Ahwan - Ahwan, Ernie Syazwanie (2013)
This report represents the idea of using Xcos simulation software to simulate the performance of non linear for closed lopp of 3 Phase Switched Reluctance Motor. Key to understanding in detail of SRM is throughout its torque equation.